The Influence Of Social Media In Marketing Communication Strategies Towards Reputation Building Of Open University Malaysia (OUM) - Syariza Isahak (2020)
The study was conducted to investigate the effectiveness of social media as a marketing communication towards reputation building of Open University Malaysia (OUM). Based on the previous studies, three factors have been identified known as content, promotion and comprehensiveness of the information. The population of this study are the students of OUM and the sample size were taken from students in Bangi Learning Centre through convenience sampling technique. This study adopts a quantitative research method approach with result of 211 respondents. To analyse the data, multiple linear regression analysis was adopted in this study. The findings of the study have shown enough evidences to support the hypotheses. All three variables indicated significant results. Comprehensive information is the highest variable perceived by the respondents, followed by promotion and content towards the reputation building of OUM. The implication of the study brings more understanding on the importance of enhancing the content, promotion and comprehensive information in the OUM social media. This will lead towards increasing the student’s enrolment and improve OUM brand equity. The conclusion of this study can be used to strengthen OUM reputation in social media as an effective marketing tool hence becoming a source of reference for students to choose Open Distance Learning (ODL) institutions to pursue their studies.(Abstract by authors)